The meaning of Marine insurance - Adamova, O. S.; Адамова, О. С.; Адамова, Е. С. (Одеса : Юрид. л-ра, 2012)
The concepts of marine insurance and founding of origin are investigated. A necessity and actuality of marine insurance are analysed as to the guarantee of calmness and economic security of the shipowner and owner of cargo and also stability of market relations. Also the analysis of existent kinds and methods of insurance was made.
Adamova O. S. The meaning of Marine insurance / O. S. Adamova // Актуальні проблеми держави і права : зб. наук. пр. /редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; МОНмолодьспорт України, НУ «ОЮА». – Одеса : Юрид. л-ра, 2012. – Вип. 66. - С. 66-71.
Keywords: marine insurance; navigator; shipowner; cargo; ship; danger; risk; favour; policy; coverage; морське страхування; мореплавство; судновласник; вантаж; судно; небезпека; ризик; послуга; поліс; покриття; морское страхование; мореходство; судовладелец; груз; судно; опасность; риск; услуга; полис; покрытие